Analisis Perilaku Konsumen dalam Menentukan Keputusan Pembelian Rumah Bersubsidi Tipe 36 (Studi Kasus PT. Borneo Real Properti) - Hermawan, Teguh; Firayanti, Yuni; Marhamah, Marhamah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study aims to analyze consumer behavior in determining the purchase decision for type 36 subsidized houses at PT Borneo Real Properti. The research employs a qualitative method, with data collection techniques including in-depth interviews, observation, and documentation. The findings reveal that factors influencing consumer purchase decisions include personal economic conditions, environmental and security factors, strategic location, as well as the quality of the buildings and facilities provided. Additionally, social factors, such as recommendations from family and friends, play a significant role in consumer decision-making. These findings provide insights for PT Borneo Real Properti to develop more effective marketing strategies and enhance customer satisfaction. A comprehensive and consumer-oriented strategy is expected to increase the company's competitiveness in the subsidized housing market.